Presidential influence versus bureaucratic discretion: president - agency relations in civil rights policy - Shull, Steven A
This research examines presidents' administrative actions in civil rights to policy and agency responses to those actions. It considers the frequent debate between presidential influence over the bureaucracy versus the more community posited model of bureaucratic discretion rsults suggests that assertive presidents like Johnson and Reagan can inflence agency actions in civil rights policy they obtain closer correspondence with their preperred policies than do less assertive presidents. Overall, however, only limited correspondence between presidential and agency actions appears because agencies have considerable discretion in their imlementing actions. Thus neither presidential influence nor bureaucratic d
Keywords: Civkl Rights; President; President - U.S.A.